IMPLEMENTASI AKUNTANSI PESANTREN DALAM MODERNISASI SISTEM PEMBUKUAN UNTUK MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS KEUANGAN PONDOK PESANTREN ASSHODIQIYAH - Sri Retnoningsih; Wulan Budi Astuti; Atiq Amjadallah Alfie; Dina Pratiwi Ikaningtyas; Qomari Yatuzzahra; Sindi Aprilia; Ahmad Bagas Setianto (Universitas Muhammadiyah Kudus, 2025)
Transparent and accountable financial management is a major challenge for many Islamic boarding schools in Indonesia, including the Asshodiqiyah Islamic Boarding School in Semarang. This community service activity aims to improve the financial governance of Islamic boarding schools through the modernization of the sharia-based accounting bookkeeping system according to the Islamic Boarding School Accounting Guidelines (PAP). This activity was carried out in February 2025 in the male hall of the Asshodiqiyah Islamic Boarding School, which was attended by the financial managers of the institution, male and female administrators of Asshodidiyah. The method used is a participatory approach in the form of training and mentoring for treasurers and Islamic boarding school administrators in understanding, classifying, and recording financial transactions systematically. The results of the activity showed an increase in participants' understanding of the principles of sharia accounting, their ability to prepare basic financial reports, and their commitment to implementing more orderly and accountable financial records. The implementation of this system also strengthens stakeholder trust and opens up opportunities for collaboration with external institutions. This bookkeeping modernization not only answers administrative needs, but also strengthens the position of Islamic boarding schools in building professional and sustainable financial governance.